Terra Sigillata from the villa of Casal do Rebolo (Sintra, Portugal) - Gonçalves, Alexandre (Rei Cretariae Romanae Fautorum Acta, 2022)
The set of sigillata recovered in both habitational and funerary areas from the villa of Casal do Rebolo (Sintra, Portugal) is now presented. The analyses of material recovered so far reveal an occupation started during the Flavian Dynasty, attested by Southern Gaul sigillata, continually extant at least until the middle of 5th century, according to the presence of African and Phocaean red slip ware imports. Materials recovered in superficial levels in the necropolis reveal the use of that area for a longer period than that attested by the excavated contexts in the graves, but one that is coherent with the chronology proposed for the utilization of the villa.